Attrition in Interpersonal Psychotherapy Among Women With Post-traumatic Stress Disorder Following Sexual Assault - Proença, Cecília R.; Markowitz, John C.; Prado, Euthymia A.; Braga, Rosaly; Coimbra, Bruno M.; Mello, Thays F.; Maciel, Mariana R.; Pupo, Mariana; Póvoa, Juliana; Mello, Andrea F.; Mello, Marcelo F. (Frontiers in Psychology, 2019)
Background An estimated 16.9% of adult Brazilian women experience sexual assault in their lifetime. Almost half of women who suffer such trauma develop post-traumatic stress disorder (PTSD). Markowitz et al. (2015) found that an affect-focused non-exposure therapy, Interpersonal Psychotherapy (IPT), adapted to treat PTSD (IPT-PTSD) had similar efficacy to and lower dropout rates than Prolonged Exposure (PE), the “gold standard,” most studied exposure therapy for PTSD. Objective To assess attrition rates in IPT of sexually assaulted women recently diagnosed with PTSD. Methods The current study derives from a two-arm, randomized controlled clinical trial of sexually assaulted women with PTSD who received 14 weeks of standardized treatment with either IPT-PTSD or sertraline. Sample: The 32 patients in the IPT treatment arm were analyzed. Results Overall attrition was 29%. One patient was withdrawn because of suicidal risk; four dropped out pre-treatment, and five dropped out during IPT-PTSD. If the excluded patient is considered a dropout, the rate increases to 31%. Discussion This is the first formal study of IPT for PTSD specifically due to sexual assault. IPT attrition approximated dropout rates in PE studies, which are often around 30%, and to the sertraline group in our study (34.5%). Further research should compare IPT and PE among sexually assaulted women to clarify our hypothesis that IPT could be an attractive alternative approach for this patient group.